UTAUT: Application of Financial Technology in Islamic Banks - Sri Andayaningsih; Indrawahyuni (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
Using the Unified Theory of Acceptance and Use of Technology (UTAUT), this research intends to examine the factors that affect Islamic banks' adoption of Fintech in Makassar City. Surveys and questionnaires filled out by a randomly selected sample of users of Fintech are being used for the study. According to the analyses conducted, there is a positive relationship between trust and intent, trust and usefulness, trust and perceived convenience, trust and attitude, knowledge and intent, knowledge and usefulness, knowledge and perceived ease, knowledge and perceived attitude, perceived usefulness and intent, perceived usefulness and intent, and perceived usefulness and perceived attitude. Users of BSI Makassar report a positive correlation between increased risk and increased intent, increased risk and increased perceived usefulness, increased risk and increased perceived convenience, and increased risk and increased attitude.